2012
DOI: 10.1038/jcbfm.2012.186
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Brain Ph with or without Hypoxia is a Marker of Profound Metabolic Derangement and Increased Mortality after Traumatic Brain Injury

Abstract: Cerebral hypoxia and acidosis can follow traumatic brain injury (TBI) and are associated with increased mortality. This study aimed to evaluate a relationship between reduced pH bt and disturbances of cerebral metabolism. Prospective data from 56 patients with TBI, receiving microdialysis and Neurotrend monitoring, were analyzed. Four tissue states were defined based on pH bt and P bt O 2 : 1-low P bt O 2 /pH bt , 2-low pH bt /normal P bt O 2 , 3-normal pH bt /low P bt O 2 , and 4-normal pH bt /P bt O 2 ). Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 44 publications
0
23
1
Order By: Relevance
“…Thus, transporter at the plasma membrane is inactivated under physiological conditions. Ischemia or traumatic brain injury that reduce extracellular pH may therefore promote glutamate efflux and excitotoxicity through this mechanism (McDonald et al, 1998; Chesler, 2003; Timofeev et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, transporter at the plasma membrane is inactivated under physiological conditions. Ischemia or traumatic brain injury that reduce extracellular pH may therefore promote glutamate efflux and excitotoxicity through this mechanism (McDonald et al, 1998; Chesler, 2003; Timofeev et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Increases in the LPR, an established marker of metabolic crisis that signals a switch from aerobic to anaerobic metabolism due to ischemia and/or mitochondrial dysfunction, 7,8 were initially thought to reflect secondary hypoxic/ischemic events. 5,6,[8][9][10][11][12] However, recent reports have shown these perturbations are more enigmatic, as severe metabolic crisis (LPR >40) is observed even after adequate resuscitation, 13 in the absence of frank ischemia, 14 and independent of cerebral perfusion pressures. 15 Vespa and colleagues have shown that non-convulsive seizures are one pathophysiological source of such a non-ischemic ''metabolic crisis.''…”
Section: Introductionmentioning
confidence: 99%
“…Such measurements in humans have been challenging technically but are critical for understanding normal brain processes, as well as the pathophysiology of a variety of brain conditions and diseases such as tumors and traumatic brain injury. [5][6][7][8][9][10][11][12][13][14]…”
mentioning
confidence: 99%